RESISTANCE TO FEMALE STEREOTYPES IN THE ANIMATED FILM MULAN (1998) - Diki Febrianto; Turita Indah Setyani (Undiksha Press, 2023)
The resistance efforts made by women against men, form attitudes and behaviors that refer to efforts to fight and oppose stereotypes against women. It is common for these efforts to be carried out with careful strategists. This research revealed the existence of resistance to female stereotypes carried out in a different way, namely through the animated film Mulan (1998) directed by Tony Bancroft and Barry Cook. The research used descriptive qualitative. Data collection in this study used montage technique and data analysis of Miles and Huberman model. The results of this study show various forms of stereotypes against women that refer to standardization. Stereotypes of women include beautifying themselves to get the right partner; behaving well to their partners and parents; having white skin like a delicate and pale lotus flower; having a small waist; being able to pour tea gracefully, calmly and humbly; being elegant; polite; gentle; not embarrassing; carrying out their duties calmly and respectfully; always thinking in their actions; being authoritative, to bring honour to their family. Mulan as an important character in this movie shows that she indirectly fights against female stereotypes. Keywords: resistance, female stereotypes, film, character, family